SHBG Gene Polymorphisms and Their Influence on Serum SHBG, Total and Free Testosterone Concentrations in Men - Walravens, Joeri; Sleumer, Bas; Vos, Michel J; Snaterse, Gido; Narinx, Nick; Antonio, Leen; Reyns, Tim; Fiers, Tom; Kema, Ido P; Kaufman, Jean-Marc; van de Merbel, Nico C; Lapauw, Bruno (The journal of clinical endocrinology and metabolism, 2025)
Genetic variation in SHBG structure may affect estimates of sex steroid exposure by altering the affinity of the protein for its ligand. Consequently, free hormone calculations assuming constant binding affinity may, for certain genetic variations, lead to incorrect diagnoses if genetic variation is not taken into consideration. To investigate the effects of genetic variation in SHBG on calculated and measured serum free testosterone (T) in men. Population-based sibling-pair study in 999 healthy men aged 25 to 45 (mean, 34.5) years. Genotyping using microarray (Illumina) for single-nucleotide polymorphism (SNPs) suggested to affect binding affinity and/or concentration of SHBG or T. SHBG concentrations were measured using immunoassay and in a subset (n = 32) by liquid chromatography-tandem mass spectrometry (LC-MS/MS). Total T was measured using LC-MS/MS. Free T was calculated and in a subset (n = 314) measured directly using LC-MS/MS after equilibrium dialysis. Allelic frequencies of analyzed SNPs ranged from 0.5% to 58.2%. Compared to wild-type, SHBG concentrations were lower in rs6258 heterozygotes (-24.7%; P < .05) and higher in rs6259 heterozygotes, rs727428 homozygotes, and carriers of rs1799941 (+10.8 to 23.1%; all P < .05). Total T was higher in rs727428 homozygotes and carriers of rs5934505, rs1799941and rs6259 (+3.9 to 21.4%; all P < .05). No clear effects on measured free T were found, except for a trend toward higher values in rs6259 homozygotes, significant for calculated free T (+18.7%; P < .05) in the larger global study population. In these men, analyzed SNPs were relatively prevalent and affected serum concentrations of total T and SHBG but not calculated or measured free T except for a higher trend in rs6259 homozygotes.